ANALISIS PEMANFAATAN APLIKASI E-PUSTAKA BANDUNG DI DINAS ARSIP DAN PERPUSTAKAAN KOTA BANDUNG - Putri Nur Nabihatul Ghofilah; Ute Lies Siti Khadijah; Fitri Perdana (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the utilization of the e-Pustaka Bandung application based on the Technology Acceptance Model (TAM), focusing on perceived usefulness and perceived ease of use. This study employed a qualitative method with a case study approach to explore users' subjective experiences. Data were collected through observation, in-depth interviews, documentation, and literature review. The findings indicate that the e-Pustaka Bandung application fulfills all indicators of perceived ease of use, as users found the application easy to learn, operate, and understand, as well as flexible and accessible anytime and anywhere. In terms of perceived usefulness, the application provides benefits in accelerating information access, increasing productivity, and facilitating reference search. However, limitations in the digital collection cause the application to be not yet optimal in supporting work performance and effectiveness, particularly for academic purposes. Overall, perceived ease of use is more dominant than perceived usefulness in users’ experiences. Therefore, regular expansion and updating of the digital collection is needed to optimize the application in meeting users’ information needs.